2019
DOI: 10.1159/000505143
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-144 Regulates Cardiomyocyte Proliferation and Apoptosis by Targeting <b><i>TBX1</i></b> through the JAK2/STAT1 Pathway

Abstract: It is currently believed that the TBX1 gene is one of the core genes of congenital heart disease (CHD). However, there are few studies on the abnormal regulation of TBX1 gene expression. The purpose of this work was to investigate the role of miR-144 and TBX1 in cardiac development by studying the regulatory relationship and mechanism of miR-144 on TBX1/JAK2/STAT1 in cardiomyocytes. Cell proliferation was detected by MTT and clone formation assay and cell cycle and apoptosis by flow cytometry. The levels of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The data of Figures 3 and 4 indicate that exposure to CoV induces plasma cell apoptosis and suppresses SOD in plasma cells. As the Janus kinase (JAK)2/STAT1 (signal transducer and activator of transcription 1) pathway activation is associated with cell apoptosis initiation [ 9 ], the JAK2/STAT1 activation in sPCs was assessed after exposing to CoV overnight. The results showed that CoV exposure markedly induced the JAK2 and STAT1 phosphorylation in sPCs (Figures 5(a) and 5(b) ).…”
Section: Resultsmentioning
confidence: 99%
“…The data of Figures 3 and 4 indicate that exposure to CoV induces plasma cell apoptosis and suppresses SOD in plasma cells. As the Janus kinase (JAK)2/STAT1 (signal transducer and activator of transcription 1) pathway activation is associated with cell apoptosis initiation [ 9 ], the JAK2/STAT1 activation in sPCs was assessed after exposing to CoV overnight. The results showed that CoV exposure markedly induced the JAK2 and STAT1 phosphorylation in sPCs (Figures 5(a) and 5(b) ).…”
Section: Resultsmentioning
confidence: 99%
“…It corroborates a prior study where Prkar2a has been indicated to reversely regulate the JAK2/STAT1 signaling pathway [ 17 ]. Notably, the activation of the JAK2/STAT1 signaling pathway has been reported to be involved in cell apoptosis [ 19 , 39 ]. Importantly, inactivated JAK2/STAT1 due to GJ-4 was found to improve memory impairment in focal CI/reperfusion in rats [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Tbx1 is currently described as one of the core genes implicated in congenital heart disease (CHD), the molecular mechanisms underlying its role in the pathogenesis of this abnormality is not fully understood [345]. Recent studies, described by Cao et al [346] showed that miR-144 inhibits cardiomyocyte proliferation and promotes cardiomyocyte apoptosis by targeting the 3 UTR of Tbx1 via regulating Jak2/Stat1 signaling pathway (Figure 3B,C).…”
Section: Post-transcriptional Control Of Aortic Arch Development By N...mentioning
confidence: 99%